The deluge: an historical novel of Poland, Sweden and Russia - Sienkiewicz, Henryk; Curtin, Jeremiah (Little, Brown and Co., 1919)
A historical novel by the Polish author Henryk Sienkiewicz, published in 1886. It is the second volume of a three-volume series known to Poles as "The Trilogy," having been preceded by With Fire and Sword (Ogniem i mieczem, 1884) and followed by Fire in the Steppe (Pan Wołodyjowski, 1888). The novel tells a story of a fictional Polish-Lithuanian Commonwealth soldier and noble Andrzej Kmicic and shows a panorama of the Commonwealth during its historical period of the Deluge, which was a part of the Northern Wars
A sequel to "With fire and sword."
Translation of: Potop.
A historical novel by the Polish author Henryk Sienkiewicz, published in 1886. It is the second volume of a three-volume series known to Poles as "The Trilogy," having been preceded by With Fire and Sword (Ogniem i mieczem, 1884) and followed by Fire in the Steppe (Pan Wołodyjowski, 1888). The novel tells a story of a fictional Polish-Lithuanian Commonwealth soldier and noble Andrzej Kmicic and shows a panorama of the Commonwealth during its historical period of the Deluge, which was a part of the Northern Wars
Also issued online.
Keywords: Polish fiction. / fast / http://id.worldcat.org/fast/1068916; Soldiers. / fast / http://id.worldcat.org/fast/1125233; Polish fiction / 19th century.; Soldiers / Fiction. / http://id.loc.gov/authorities/subjects/sh2008111377; Poland. / fast / http://id.worldcat.org/fast/1206891; Poland / History / John II Casimir, 1648-1668 / Fiction.; Fictional Work. / http://id.nlm.nih.gov/mesh/D022922; Novels. / lcgft / http://id.loc.gov/authorities/genreForms/gf2015026020; Novels. / fast / http://id.worldcat.org/fast/1921742; History. / fast / http://id.worldcat.org/fast/1411628; Fiction. / fast / http://id.worldcat.org/fast/1423787